Rethinking Transnationalism in the Era of Globalization - Paudel , Maheswor (Myagdi Guru, 2022)
This paper examines the growing influence of transnationalism on a number of academics, sociologists, anthropologists, economists and political theorists for the last three decades. Critically analyzing ideas expressed by some prominent research scholars such as Steven Vertovec, Patricia Clavin, Masao Miyoshi, Daniel Mato and Paul Jay, this paper aims at exploring the concepts and developments of this new field that has been closely linked with globalization and deterritorialization. By assessing the prominence of transnationalism in various disciplines, this paper reaches the conclusion that literature, like culture, society, economy and politics, cannot remain exempt from the waves of global forces as literature in today’s world is more an expression of transnational encounters than the record of ‘national’ experiences alone.